Koordinasi Dinas Perhubungan dan Satuan Lalu Lintas Dalam Pengaturan Lalu Lintas di Kota Bandar Lampung - Putu Febriawan (Journal of Politics and Democracy, 2026)
Traffic congestion is a serious problem commonly encountered in urban areas such as Bandar Lampung City. To address this issue, the Bandar Lampung City Transportation Agency and the Traffic Unit of the Bandar Lampung City Police coordinate traffic management activities across the city. This study aims to describe the coordination between the Traffic Division of the Bandar Lampung City Transportation Agency and the Traffic Unit of the Bandar Lampung City Police in managing traffic. This study employed a qualitative method supported by several sources of data obtained through interviews, observation, and documentation. The data were analyzed using the framework proposed by Miles et al. (2014), which consists of data condensation, data display, and conclusion drawing. The findings indicate that coordination between the Traffic Division of the Bandar Lampung City Transportation Agency and the Traffic Unit of the Bandar Lampung City Police has not been fully effective based on the four aspects of coordination proposed by Hasibuan (2006). Unity of action has been implemented effectively, although synchronization in the timing of traffic management activities remains suboptimal. Meanwhile, communication, division of work, and discipline still show several weaknesses, particularly in joint evaluation and task implementation.